Reinforced polyamide material with high low-temperature impact resistance and preparation method thereof

By using bifunctional group compounds in polyamide materials for toughening modification, the low-temperature impact resistance of polyamide materials is improved, and the problem of insufficient performance in the prior art is solved. It is suitable for high-performance packaging and electronic materials fields.

CN119219857APending Publication Date: 2024-12-31HENAN GREENPUS NEW MATERIAL TECH CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411340317.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-25
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

Existing polyamide materials have insufficient performance in terms of heat resistance and impact strength, and it is difficult for the modification method to simultaneously improve the tensile strength, bending strength, heat resistance, fluidity and notch impact strength of the material, while maintaining the stability of other performance indicators. sex.

Method used

Using bifunctional group compounds containing amino groups and end-position olefins as toughening modifiers, react with the amide bond of polyamide and polymerize with ethylene-octene copolymer to form a bidirectional graft structure to improve the polyamide material Resistant to low temperature shock.

Benefits of technology

It significantly improves the impact performance of polyamide materials and is suitable for low-voltage electrical shells, junction boxes, switches and other electronic and electrical components, improving the overall performance indicators of the materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005059492830000021
    Figure BDA0005059492830000021
  • Figure BDA0005059492830000051
    Figure BDA0005059492830000051
  • Figure FDA0005059492800000011
    Figure FDA0005059492800000011
Patent Text Reader

Abstract

The invention discloses a reinforced polyamide material with high low-temperature impact resistance and a preparation method thereof, and belongs to the field of material preparation. The material comprises polyamide 6, glass fibers, an ethylene-octylene copolymer, a toughening modifier, an antioxidant and a lubricant. The preparation method comprises the following steps: drying polyamide 6, glass fiber and ethylene-octylene copolymer in a vacuum drying oven to constant weight; adding the dried materials into a vertical high-speed mixer, and mixing until the materials are uniform; adding the mixed material into a double-screw extruder, extruding, feeding into water, cooling, drawing, and pelletizing; and finally, drying the diced materials in vacuum until the weight is constant. According to the invention, the bifunctional compound toughening modifier simultaneously containing amino and terminal olefin is added, the amino exchange reaction of amide is carried out between the amino and an amido bond on PA6, and a polymerization reaction is carried out between a terminal carbon-carbon double bond and a polyolefin material under the catalysis of an initiator, so that the effect of bidirectional grafting is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to material preparation, in particular to a reinforced polyamide material with high low-temperature impact resistance and a preparation method thereof. Background Art

[0002] Polyamide, commonly known as nylon, is a thermoplastic resin. Its molecular structure is characterized by a chain or network polymer composed of repeated amide units. It has excellent mechanical strength, wear resistance, self-lubrication, corrosion resistance and good molding processability. It can be processed into injection molded parts to replace metals. It has application scenarios in the fields of automobiles, electrical appliances, home appliances, aerospace, chemical industry, military industry, etc. Polyamide materials have insufficient heat resistance and impact strength, and their dimensional stability and electrical properties need to be improved.

[0003] Polyamide 6, also known as polycaprolactam or nylon 6 (PA6), is a translucent to opaque yellowish or milky white thermoplastic resin. There are many preparation methods. According to the polymerization mechanism, it can be divided into hydrolysis polymerization, solid phase polymerization and ion polymerization. The current development trend of polyamide 6 polymerization technology is the combination of hydrolysis polymerization and solid phase polymerization. In order to meet the requirements for the performance of polyamide 6 materials in the fields of high-performance packaging, electronic materials, and high-strength fiber applications, the modification technology of polyamide 6 (PA6) has attracted people's attention. The modification methods reported so far include physical and chemical methods, such as toughening modification, fiber reinforcement modification, copolymerization modification, nanocomposite modification, etc. However, the polyamide materials prepared by general modification methods cannot simultaneously improve the tensile strength, flexural strength, heat resistance, fluidity, and notched impact strength of the materials, and the influence of different modification methods on the performance of polyamide is also different. This requires the use of specific modification methods to improve the expected performance of modified polyamide materials, while at the same time minimizing the reduction of other performance indicators of polyamide. Blending modification is an effective method to improve the shortcomings of nylon performance. Researchers have been conducting research in this area for many years, including strengthening nylon, PA / PE, PA / ABS, PA / PPO and other nylon alloys, improving the impact strength of nylon at low temperature and dry state and reducing hygroscopicity, and improving the heat resistance of nylon and improving comprehensive performance. Simply adding modifiers often fails to achieve the effect of synergistic enhancement due to the poor compatibility between different types of materials. Use polyethylene or octene materials and add them directly to PA6. Since olefin polymers have no polar groups, their compatibility is poor after being added to PA6, and they are easy to delaminate and have obvious interfaces. Therefore, the performance improvement of PA6 is limited. At present, there are many literature reports that use modified PE or PP to achieve the purpose of modifying PA6 through hot melt extrusion. The general modifier is anhydride or carboxylic acid compound. Its purpose is to enhance its polarity after grafting PE or PP, so as to have better compatibility with PA6. The grafting rate of this modification method is generally low, and there is no chemical bond between the modified polyolefin material and PA6, resulting in poor product performance stability and limited performance improvement.

[0004] At present, the special materials for electrical components require high rigidity, good heat resistance and dimensional stability, as well as good processability and flame retardancy. However, directly using existing general-purpose resin materials is not ideal, and it is necessary to further improve the performance of the materials and modify them to meet the product requirements. Summary of the invention

[0005] Purpose of the invention: The purpose of the present invention is to provide a reinforced polyamide material with high low-temperature impact resistance; another purpose of the present invention is to provide a method for preparing a reinforced polyamide material with high low-temperature impact resistance.

[0006] Technical solution: A reinforced polyamide material with high low-temperature impact resistance, including polyamide 6, glass fiber, ethylene-octene copolymer, toughening modifier, antioxidant, and lubricant;

[0007] Wherein, the toughening modifier is composed of a compound of formula 1 and an initiator.

[0008]

[0009] In the compound of formula 1, R is selected from cyclohexyl, aryl and benzyl.

[0010] Preferably, the material comprises, by weight, 650 to 86 parts of polyamide, 5 to 20 parts of glass fiber, 3 to 20 parts of ethylene-octene copolymer, 5 to 10 parts of toughening modifier, 0.1 to 0.3 parts of antioxidant, and 0.3 to 1.0 parts of lubricant.

[0011] Preferably, the viscosity of the base resin of polyamide 6 is 2.4-3.2 Pa.S.

[0012] Preferably, the initiator is benzoyl peroxide, and the mass ratio of the compound of formula 1 to the initiator is 98:1-2.

[0013] Preferably, the antioxidant is one or a mixture of two or more of organic amine, phosphite, and thioester antioxidants.

[0014] Preferably, the lubricant is fatty acid, stearate, fatty amide, etc., and the stearate is various divalent metal salts or trivalent metal salts such as zinc, calcium, aluminum, etc.

[0015] A method for preparing a reinforced polyamide material with high low-temperature impact resistance comprises the following steps:

[0016] S1. Place polyamide 6, glass fiber, and ethylene-octene copolymer in a vacuum drying oven and dry at 90-100° C. to constant weight;

[0017] S2, adding 650-86 parts of dried polyamide, 5-20 parts of glass fiber, 3-20 parts of ethylene-octene copolymer, 5-10 parts of toughening modifier, 0.1-0.3 parts of antioxidant, and 0.3-1.0 parts of lubricant into a vertical high-speed mixer, and mixing until uniform;

[0018] S3, adding the mixed material in step S2 into a twin-screw extruder, and after extrusion, sending it into 15-45°C water for cooling, drawing and pelletizing;

[0019] S4, drying the pelletized material in step S3 at 90-100°C in vacuum until constant weight.

[0020] Preferably, in step S2, the temperature of a feeding section of the twin-screw extruder is 210° C. and maintained for 2 to 4 hours, the temperature of the other sections is 230 to 250° C., and the screw speed is 150 r / min.

[0021] Beneficial effects: The present invention adds a bifunctional compound toughening modifier containing both an amino group and a terminal olefin, utilizes its amino group to undergo an amide exchange reaction with the amide bond on PA6, and at the same time, the terminal carbon-carbon double bond can undergo a polymerization reaction with a polyolefin material under the catalysis of an initiator, thereby achieving a two-way grafting effect and realizing the toughening modification of PA6 by ethylene-octene copolymer. The impact performance of the reinforced polyamide material prepared by the present invention is greatly improved, which will be greatly beneficial to its application in electronic and electrical component products such as low-voltage electrical appliance housings, junction boxes, connectors, switches, etc. DETAILED DESCRIPTION

[0022] In order to make the technical solution of the present invention clearer, the present invention is further described in detail below in conjunction with specific embodiments.

[0023] Example 1

[0024] Accurately weigh 57.5 kg of PA6 particles (HY-2500A), 15 kg of glass fiber (ECS301HP-3), and 15 kg of ethylene-octene copolymer (N406), and place them in a 95°C vacuum drying oven for 8 hours; add the dried materials, 5 kg of 1-cyclohexylbut-3-ene-1-amine, 0.05 kg of benzoyl peroxide, 0.1 kg of amine antioxidant, and 0.3 kg of zinc stearate into a vertical high-speed mixer and mix for 1-2 hours; add the mixed materials into a twin-screw extruder, set the temperature of one section to 210°C, and keep it for 3 hours; the temperature of other sections is 230-230-240-250°C, the screw speed is 150 r / min, and after extrusion, it is sent into 25°C water for cooling, drawing, and pelletizing; the above-mentioned pelletized material is placed in a 90°C vacuum drying oven and dried for 10 hours to obtain a reinforced polyamide material 1.

[0025] Example 2

[0026] Accurately weigh 57.5 kg of PA6 particles (HY-2500A), 15 kg of glass fiber (ECS301HP-3), and 10 kg of ethylene-octene copolymer (N406), and place them in a 95°C vacuum drying oven to dry for 8 hours; add the dried materials, 5 kg of 1-cyclohexylbut-3-ene-1-amine, 0.05 kg of benzoyl peroxide, 0.1 kg of amine antioxidant, and 0.3 kg of zinc stearate into a vertical high-speed mixer and mix for 1-2 hours; add the mixed materials into a twin-screw extruder, set the temperature of one section to 210°C, and keep it for 3 hours; the temperature of other sections is 230-230-240-250°C, the screw speed is 150 r / min, and after extrusion, it is sent into 25°C water for cooling, drawing, and pelletizing; the above-mentioned pelletized material is placed in a 90°C vacuum drying oven and dried for 10 hours to obtain reinforced polyamide material 2.

[0027] Example 3

[0028] Accurately weigh 57.5 kg of PA6 particles (HY-2500A), 15 kg of glass fiber (ECS301HP-3), and 5 kg of ethylene-octene copolymer (N406), and place them in a 95°C vacuum drying oven to dry for 8 hours; add the dried materials, 10 kg of 1-phenylbut-3-ene-1-amine, 0.05 kg of benzoyl peroxide, 0.1 kg of amine antioxidant, and 0.3 kg of zinc stearate into a vertical high-speed mixer and mix for 1-2 hours; add the mixed materials into a twin-screw extruder, set the temperature of one section to 210°C, and keep it for 3 hours; the temperature of other sections is 230-230-240-250°C, the screw speed is 150 r / min, and after extrusion, it is sent into 25°C water for cooling, drawing, and pelletizing; the above-mentioned pelletized material is placed in a 90°C vacuum drying oven and dried for 10 hours to obtain reinforced polyamide material 3.

[0029] Comparative Example 1

[0030] Accurately weigh 57.5 kg of PA6 particles (HY-2500A), 15 kg of glass fiber (ECS301HP-3), and 15 kg of maleic anhydride grafted POE (N406), and place them in a 95°C vacuum drying oven to dry for 8 hours; add the dried materials, 0.1 kg of amine antioxidant, and 0.3 kg of zinc stearate into a vertical high-speed mixer and mix for 1-2 hours; add the mixed materials into a twin-screw extruder, set the temperature of one section to 210°C, and keep it for 3 hours; the temperature of other sections is 230-230-240-250°C, the screw speed is 150 r / min, and after extrusion, it is sent into 25°C water for cooling, drawing, and pelletizing; the above-mentioned pelletized material is placed in a 90°C vacuum drying oven and dried for 10 hours to obtain reinforced polyamide material 4.

[0031] Comparative Example 2

[0032] Accurately weigh 57.5 kg of PA6 particles (HY-2500A), 15 kg of glass fiber (ECS301HP-3), and 15 kg of maleic anhydride grafted POE (FUSABOND N493), and place them in a 95°C vacuum drying oven to dry for 8 hours; add the dried materials, 0.1 kg of amine antioxidant, and 0.3 kg of zinc stearate into a vertical high-speed mixer and mix for 1-2 hours; add the mixed materials into a twin-screw extruder, set the temperature of one section to 210°C, and keep it for 3 hours; the temperature of other sections is 230-230-240-250°C, the screw speed is 150 r / min, and after extrusion, it is sent into 25°C water for cooling, drawing, and pelletizing; the above-mentioned pelletized material is placed in a 90°C vacuum drying oven and dried for 10 hours to obtain reinforced polyamide material 4.

[0033] Comparative Example 3

[0034] Accurately weigh 57.5 kg of PA6 particles (HY-2500A), 15 kg of glass fiber (ECS301HP-3), and 15 kg of maleic anhydride grafted SEBS (KT-7), and place them in a 95°C vacuum drying oven to dry for 8 hours; add the dried materials, 0.1 kg of amine antioxidant, and 0.3 kg of zinc stearate into a vertical high-speed mixer and mix for 1-2 hours; add the mixed materials into a twin-screw extruder, set the temperature of one section to 210°C, and keep it for 3 hours; the temperature of other sections is 230-230-240-250°C, the screw speed is 150 r / min, and after extrusion, it is sent into 25°C water for cooling, drawing, and pelletizing; the above-mentioned pelletized material is placed in a 90°C vacuum drying oven and dried for 10 hours to obtain reinforced polyamide material 6.

[0035] Impact strength: refer to GB / T 1043.1-2008 test specimen notch impact strength, the notch specimen section is 8mm×4mm, V-shaped notch, notch depth is 2mm, and the pendulum is selected as 11J. The test results of the embodiment and comparative example materials are shown in Table 1:

[0036] Table 1 Test results of examples and comparative examples

[0037]

[0038] The above results show that as the temperature decreases, the notched impact strength decreases; the polyamide material prepared by adding a bifunctional toughening modifier using the technical solution of the present invention has a 55% increase in notched impact strength over the polyamide material toughened by a commercial single-modified polyolefin material, showing a huge advantage.

[0039] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A reinforced polyamide material with high low temperature impact resistance, characterized in that: Including polyamide 6, glass fiber, ethylene-octene copolymer, toughening modifier, antioxidant, lubricant; Wherein, the toughening modifier is composed of a compound of formula 1 and an initiator. In the compound of formula 1, R is selected from cyclohexyl, aryl and benzyl.

2. The reinforced polyamide material with high low-temperature impact resistance according to claim 1, characterized in that: The material comprises, by weight, 650-86 parts of polyamide, 5-20 parts of glass fiber, 3-20 parts of ethylene-octene copolymer, 5-10 parts of toughening modifier, 0.1-0.3 parts of antioxidant and 0.3-1.0 parts of lubricant.

3. The reinforced polyamide material with high low-temperature impact resistance according to claim 1, characterized in that: The viscosity of the base resin of polyamide 6 is 2.4 to 3.2 Pa.S.

4. The reinforced polyamide material with high low-temperature impact resistance according to claim 1, characterized in that: The initiator is benzoyl peroxide, and the mass ratio of the compound of formula 1 to the initiator is 98:1-2.

5. The reinforced polyamide material with high low-temperature impact resistance according to claim 1, characterized in that: The antioxidant is one or a mixture of two or more of organic amine, phosphite and thioester antioxidants.

6. The reinforced polyamide material with high low-temperature impact resistance according to claim 1, characterized in that: The lubricant is fatty acid, stearate, fatty amide, etc. The stearate is various divalent metal salts or trivalent metal salts such as zinc, calcium, aluminum, etc.

7. A method for preparing a reinforced polyamide material with high low-temperature impact resistance as claimed in any one of claims 1 to 6, characterized in that: The following steps are involved: S1. Place polyamide 6, glass fiber, and ethylene-octene copolymer in a vacuum drying oven and dry at 90-100° C. to constant weight; S2, adding 650-86 parts of dried polyamide, 5-20 parts of glass fiber, 3-20 parts of ethylene-octene copolymer, 5-10 parts of toughening modifier, 0.1-0.3 parts of antioxidant, and 0.3-1.0 parts of lubricant into a vertical high-speed mixer, and mixing until uniform; S3, adding the mixed material in step S2 into a twin-screw extruder, and after extrusion, sending it into 15-45°C water for cooling, drawing and pelletizing; S4, drying the pelletized material in step S3 at 90-100°C in vacuum until constant weight.

8. The method for preparing a reinforced polyamide material with high low-temperature impact resistance according to claim 7, characterized in that: In step S2, the temperature of the feeding section of the twin-screw extruder is 210° C., which is maintained for 2 to 4 hours, and the temperature of the other sections is 230 to 250° C., and the screw speed is 150 r / min.

Citation Information

Cited By

  • Mining light polymer conveyor scraper and preparation method thereof

    CN121317326A